Toxic Elements Leachability Tests on Light Weight Fly Ash Bricks - CENGIZLER, HAKAN (Asian Journal of Chemistry, 2010)
In present work, a series of batch leach tests were carried out to investigate the leachability of some toxic elements contained in the light weight fly ash bricks. The primary aim of these tests was to find out whether the light weight fly ash bricks were environmentally safe. The tests simulating the acid rain environment and natural rain water were conducted to gain insight regarding the behaviour of the elements during weathering. The light weight fly ash bricks were tested using the TCLP method and ASTM method A extraction to determine their toxicity levels.